"No One Will Speak for Us": Empowering Undocumented Immigrant Women Through Policy Advocacy. Issue 1 (2nd January 2017) - Gates, Alice B.
ABSTRACT: This article draws on data from an exploratory study involving an organized group of Mexican immigrant mothers engaged in community-based policy advocacy in the Pacific Northwest. Participants in the project lobbied state legislators on bills expanding the rights of undocumented immigrants—most notably, bills granting access to in-state tuition and driver's licenses. In-depth interviews (n=12) reveal that through this process, participants came to see themselves as political subjects, despite their unauthorized legal status. Findings reveal that participants' engagement in the policy process is centered on the idea of expressing needs and reflects their interest in improving individual, family, and community well-being. In this sense, their participation in politics flows from their roles as mothers and caregivers. By illuminating the experiences of a group—undocumented immigrant women—often overlooked in research on immigration policy and practice, this case offers a counter-narrative to the dominant portrayal of immigrant women and suggests ways to integrate community organizing and collective action into policy practice.